Peripheral ulcerative keratitis associated with chronic malabsorption syndrome and miliary tuberculosis in a child - Tarun Arora; Namrata Sharma; Adarsh Shashni; Jeewan S Titiyal (Oman Journal of Ophthalmology, 2015)
A 16-year-old girl presented with pain, redness, watering, and blurring of vision in her right eye. Slit lamp examination revealed the presence of peripheral ulcerative keratitis (PUK) and nodular scleritis. On clinical examination, the patient had stunted growth, low body mass index, and enlarged axillary nodes. Giardia cysts were present in the stool sample and histopathology of axillary lymph nodes showed caseating necrosis suggestive of tuberculosis (TB). A diagnosis of PUK with chronic malabsorption syndrome secondary to giardiasis and miliary TB was made. Oral metronidazole, anti-tubercular treatment, high protein diet and vitamin supplements were started. Topical steroids were started for peripheral ulcerative lesions following, which the PUK resolved.